The association between procalcitonin and acute kidney injury in patients stung by wasps - Zhang, Xuepeng; Feng, Yunxia; Wang, Kai; Qiu, Tong; Zhou, Jiangyuan; Che, Guowei; Chen, Siyuan; Ji, Yi (Frontiers in Physiology, 2023)
The aim of this study was to investigate the status of serum procalcitonin (PCT) in patients stung by wasps and evaluate the association between PCT levels and acute kidney injury (AKI).Patients stung by wasps admitted to two tertiary hospitals between January 2017 and December 2020 were screened for enrollment. We evaluated serum PCT levels on admission in patients stung by wasps. The patients were divided into an AKI group and a non-AKI group. A logistic regression model was used to analyze the association between PCT status and AKI. The performance of PCT concentrations in predicting the occurrence of AKI was evaluated by the area under the receiver operating characteristic curve (AUROC).Results: A total of 138 patients were enrolled, and 66 patients suffered AKI. PCT levels were elevated in 78.99% of patients stung by wasps. Nearly half of the patients (47.83%) developed AKI. PCT levels were correlated with creatinine levels on admission (r = 0.787, 95% CI: 0.713-0.844). PCT levels in patients with AKI were higher than those in patients without AKI (P<0. 001). After adjustment for covariates, PCT levels on admission were independently associated with AKI (OR: 1.575, 95% CI: 1.071-2.317, P = 0.021). The AUROC of PCT levels on admission was 0.837 (95% This is a provisional file, not the final typeset article CI, 0.771-0.902, P<0.001). A PCT level of 0.57 μg/L was the cutoff for maximizing the Youden index; the specificity was 79.45%, and the sensitivity was 73.43%.Serum PCT levels may be a potential biomarker of AKI in patients stung by wasps.